PENTINGNYA PEMBELAJARAN MULTIKULTURAL PADA PENDIDIKAN ANAK USIA DINI - Sutarto, Joko (Fakultas Ilmu Pendidikan, Universitas Negeri Semarang, 2010)
The Multiculturalism problema isnÃ¢â¬â¢t only the Indonesion but also globalÃ¢â¬â¢s problem. Multiculturalism is one of the problem key in the world which is crucial, including Indonesia, in facing the global changes in the future, evenmore the national history in past time which apparent and controlled by the hardness. It gives priority to the uniformity which is like the sociopolitical order in Indonesia since 1965. Multicultural learning has been given to the child since early aging, it will give the initial understanding which decide very much, because itÃ¢â¬â¢s golden age phase, this phase plays an important role to the development in adult time. Education of early aging child, in practical is materialized trough the kindergarden, play group, children storage place, and the others, which the programmes are variety and packed into informational institutional, and the effort which is looked so important in framework to give undertanding about multicultural concept trough the education of early aging child (PAUD). Kata Kunci: pembelajaran multikultural; pendidikan anak usia dini